Intrapartum fetal heart rate monitoring interpretation in labour: a critical appraisal. - Maso, G; Piccoli, M; De Seta, F; Parolin, S; Banco, R; Camacho Mattos, L; Bogatti, P; Alberico, S (Minerva Ginecol, 2015)
Electronic fetal monitoring (EFM) has been introduced in the obstetrics practice as a test to identify the first signs of fetal deterioration, allowing a prompt intervention to reduce neonatal morbidity and mortality. However, results from clinical trials fail to demonstrate a clear benefit with the use of EFM. No decrease in the incidence of cerebral palsy due to intrapartum asphyxia has been achieved and a significant increase in the rate of operative deliveries and in medico-legal litigations has been observed instead. Despite the lack of evidence supporting its safety and effectiveness, this method is routinely used in the clinical practice and periodical updated guidelines to standardize the method of interpretation and proper actions are proposed. However, limitations still exist and the unavoidable consequences are the increasing rate of caesarean delivery, partly due to a defensive attitude in medical choices, and medico-legal litigations for presumed inappropriate evaluation in case of perinatal adverse event. While Obstetrics Societies are trying to "fight" the rise in caesarean section rates, intrapartum EFM tracings are taken in the court proceedings as one of the main evidences in case of adverse event. The aim of this review is to discuss the limitations of guidelines dealing with intrapartum EFM and the pathophysiological basis to assess the suspicious tracings which represent the most observed and critical issue of EFM interpretation.